Application of discrete wavelet transform and back-propagation neural network for internal and external fault classification in transformer - Ngaopitakkul, Atthapol; Jettanasen, Chaiyan; Asfani, Dimas Anton; Negara, Yulistya (My University, 2019)
This paper proposes an algorithm for internal and external fault discrimination in the three-phase two-winding power transformer based on a combination of discrete wavelet transform (DWT) and back-propagation neural network (BPNN). The maximum ratio obtained from division algorithm between DWT coefficient value of differential current and zero sequence component in post-fault condition differential current signals is employed as an input for the training pattern for BPNN in order to discriminate between internal fault and external short circuit. The proposed algorithm performance has been test using various cases studies based on Thailand electricity transmission and distribution systems data. Results show that the proposed technique can achieved satisfy accuracy for internal and external fault detection and discrimination in the considered system. This methodology and result can be used to further improve protection system of power transformer in the future.
Keywords: Back-propagation neural network; External short circuit; Internal winding fault; Power transformer; Wavelet transform